South Galactic Cap u-band Sky Survey (SCUSS): Project Overview. (April 2016) - Zhou, Xu; Fan, Xiao-Hui; Fan, Zhou; He, Bo-Liang; Jiang, Lin-Hua; Jiang, Zhao-Ji; Jing, Yi-Peng; Lesser, Michael; Ma, Jun; Nie, Jun-Dan; Shen, Shi-Yin; Wang, Jia-Li; et al.
Abstract: The South Galactic Cap u -band Sky Survey (SCUSS) was established in 2009 in order to provide a photometric input catalog for target selection of the Large Sky Area Multi-Object Fiber Spectroscopic Telescope (LAMOST) project. SCUSS is an international cooperative project between National Astronomical Observatories, Chinese Academy of Sciences, and Steward Observatory at the University of Arizona, using the 90 inch (2.3m) Bok telescope on Kitt Peak. The telescope is equipped with a prime focus camera that is composed of a mosaic of four 4096 × 4096 CCDs and has a field of view of about 1 deg 2 . From 2009 to 2013, SCUSS performed a sky survey of an approximately 5000 deg 2 field of the South Galactic Cap in u band, including the Galactic anticenter area and the SDSS-IV extended imaging area. The limiting magnitude of SCUSS is deeper than 23 mag (at a signal-to-noise ratio of 5). In this paper, we briefly describe the goals of this project, method of observations and data reduction, and we also introduce current and potential scientific activities related to the SCUSS project.